MENGUNGKAP PRAKTIK AKUNTABILITAS DAN PRINSIP KEMANDIRIAN PADA PENGELOLAAN YAYASAN KAKI KITA SUKASADA BERBASIS KONSEP SOCIAL ENTREPRENEURSHIP (KEWIRAUSAHAAN SOSIAL) - Made Sintya Ega Yani; Ni Wayan Yulianita Dewi (Universitas Pendidikan Ganesha, 2022)
This study aims to gain an understanding of 1) the practice of accountability for the management of the Kaki Kita Sukasada Foundation 2) the principle of independence in the management of the Kaki Kita Sukasada Foundation. This study uses qualitative research methods involving the management of the Kaki Kita Sukasada Foundation, employees of the foundation's business unit, donors and beneficiaries of the foundation's social programs. Data were obtained through interviews, documentation studies, and observations. Data analysis was carried out through stages of activities which included data reduction, data presentation and drawing conclusions. The results of this study indicate that: 1) in terms of the accountability dimension, the Kaki Kita Sukasada Foundation has implemented it well, but in the practice of financial management accountability is still carried out in a simple manner, the foundation's management has moral responsibility, integrity, honesty, thus creating great trust in donor 2). The principle of independence in the foundation's business unit indicates that the foundation's management wants to have independent sources of funds to fund the foundation's social activities